2020
DOI: 10.1093/jnci/djaa073
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Microenvironment Immune Response in Pancreatic Ductal Adenocarcinoma Patients Treated With Neoadjuvant Therapy

Abstract: Background Neoadjuvant FOLFIRINOX and chemoradiation have been utilized to downstage borderline and locally advanced pancreatic ductal adenocarcinoma (PDAC). Whether neoadjuvant therapy-induced tumor immune response contributes to the improved survival is unknown. Therefore, we evaluated whether neoadjuvant therapy induces an immune response towards PDAC. Methods Clinicopathologic variables were collected for surgically resec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 45 publications
4
49
0
Order By: Relevance
“…Recently, results from the phase 2a COMBAT trial suggested that chemotherapy concurrent with combined anti-PD-1 and anti-C-X-C motif chemokine receptor (CXCR)4 may augment chemotherapeutic effects after attaining an mOS of 7.8 months from the start of immunotherapy in pre-treated mPDAC patients [49]. Results from both trials are in line with the expanding recognition that cytotoxic drugs (i.e., chemotherapy) can enhance immunotherapeutic effects by stimulating immunogenic tumor cell death, reducing tumor-induced immune suppression and increasing effector T cell function and infiltration [53][54][55]. Definitive advice regarding combined treatment with chemotherapy (gemcitabine/paclitaxel or FOLFIRINOX) and anti-PD-1 may be provided by two large RCTs (ClinicalTrials.gov Identifier: NCT04674956; NCT03983057).…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 74%
“…Recently, results from the phase 2a COMBAT trial suggested that chemotherapy concurrent with combined anti-PD-1 and anti-C-X-C motif chemokine receptor (CXCR)4 may augment chemotherapeutic effects after attaining an mOS of 7.8 months from the start of immunotherapy in pre-treated mPDAC patients [49]. Results from both trials are in line with the expanding recognition that cytotoxic drugs (i.e., chemotherapy) can enhance immunotherapeutic effects by stimulating immunogenic tumor cell death, reducing tumor-induced immune suppression and increasing effector T cell function and infiltration [53][54][55]. Definitive advice regarding combined treatment with chemotherapy (gemcitabine/paclitaxel or FOLFIRINOX) and anti-PD-1 may be provided by two large RCTs (ClinicalTrials.gov Identifier: NCT04674956; NCT03983057).…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 74%
“…In conclusion, crude measurement of the tumour stroma content might be insufficient for the purpose of prognostication, and it is likely that other stromal qualities, including mechanical features, extracellular matrix components or immune cell composition have overriding importance in the tumorigenic process [ 6 , [32] , [33] , [34] ]. Nevertheless, we believe that our comprehensive analysis contributes, on an elementary level, with novel perspectives on the tumour-stroma interaction and serves as a strong starting point for further focused studies aimed at elucidating the role of the tumour stroma fraction in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Isolation and identification of EVs: miR-21-5p is upregulated in M2 macrophage-derived EVs Infiltration of M2 macrophages is closely connected with the inferior prognosis of PaCa (Michelakos et al 2020), and M2 macrophage-derived EVs can promote the functions of PaCa cells (Yin et al 2020). In the experiment, THP-1 cells were induced to polarize into M2 macrophages, which were elliptical and grew aggregately ( Fig.…”
Section: Resultsmentioning
confidence: 99%